Immediate Effect of Dry Needling at Myofascial Trigger Point on Hand Spasticity in Chronic Post-stroke Patients: A Multicenter Randomized Controlled Trial - Zhang, Zengqiao; Wang, Wu; Song, Yongjia; Zhai, Tianjun; Zhu, Yan; Jiang, Liming; Li, Qunfeng; Jin, Lei; Li, Kunpeng; Feng, Wei (Frontiers in Neurology, 2021)
Background: Hand spasticity after stroke has been implicated in the rehabilitation of hand function. Immediate relief of spasticity potentially creates conditions for later rehabilitation training, which has far-reaching significance in the smooth transition of patients to the recovery period. Objective: To evaluate the immediate effect of dry needling at myofascial trigger point on hand spasticity in stroke patients. Methods: We divided 210 participants randomly into dry needling group (DN, N=70), sham dry needling group (SDN, N=70), and control group (N=70). Subjects in the DN group were treated with dry needling at myofascial trigger point five times (30min each time) every week for 4 weeks. Subjects in the SDN group were manipulated the same way as in the DN group, except that the acupuncture site was located in the area adjacent to the myofascial trigger point, which constituted a sham dry needling. We administered routine rehabilitation treatment in these two groups and the control group. The primary evaluation index was the immediate effect of hand spasticity relief. The indicators for secondary evaluation included the cumulative effect, and the change of flexion angles of the wrist, thumb, and fingers 2-5. Results: The immediate effective rate of spasticity relief (wrist, thumb, and fingers 2-5) of patients with different degrees of spasticity in the DN group was higher than that in the control and SDN groups (P<0.05). The effective rate of spasticity relief from baseline to 4 weeks in the DN group was higher than that in the control group and SDN groups (P<0.05). No difference in immediate and cumulative effect between the control group and SDN group was reported. The change of joints flexion angles in resting position before and after each treatment in the DN group was higher than that in the control and SDN groups (P<0.05), while P> 0.05 for comparisons between the control group and SDN group. At 4 weeks, although the change in the DN group was higher than that in the control group and SDN group, this difference was not statistically significant (P > 0.05). Conclusion: Dry needling can relieve varying degrees of hand spasticity instantly in post-stroke.